Implementasi Terapi Musik Dan Aromaterapi Lavender Untuk Mengurangi Nyeri Pada Pasien Fraktur Post ORIF - Rizqi Hardhanti (Infomasi dan Promosi Kesehatan, 2023)
ORIF postoperative fracture patients often cause nursing problems, comfort disorders, namely the onset of pain, management in pain patients consists of pharmacology (analgetic administration) and non-pharmacology (music therapy and lavender aromatherapy. This study aimed to determine the effect of musik therapy and lavender aromatherapy to reduce pain in post-ORIF fracture patients. The method used in this study is descriptive research with a case study method approach that explores Nursing Care in ORIF post-fracture patients. The instrument used is PQRST Pain mnemonics. In this study, a combination intervention of standard therapy (analgetic administration) with music therapy and lavender aromatherapy was given for 3 days 1 time a day. On the first and second days analgesic was given at 08.00 WIB and music therapy and aromatherapy was given for 30 minutes given at 10.30 WIB. On the third day, analgetics were given at 16.00 WIB and music therapy and aromatherapy were given at 18.30 WIB. The results of this study obtained a scale of 6 which showed that patients experienced pain during postoperative surgery. After a combination of standard therapy (analgetic administration) with music therapy and aromatherapy as much as 1 time a day within 3 days with a duration of 30 minutes can reduce the pain level score to 3. The intervention used for pain, namely a combination of standard therapy (analgetic administration) with music therapy and lavender aromatherapy, is effective for reducing pain in post-ORIF patients with fractures.